A Four-Cell-Senescence-Regulator-Gene Prognostic Index Verified by Genome-Wide CRISPR Can Depict the Tumor Microenvironment and Guide Clinical Treatment of Bladder Cancer - Sun, Jian-Xuan; Liu, Chen-Qian; Xu, Jin-Zhou; An, Ye; Xu, Meng-Yao; Zhong, Xing-Yu; Zeng, Na; Ma, Si-Yang; He, Hao-Dong; Zhang, Zong-Biao; Wang, Shao-Gang; Xia, Qi-Dong (Frontiers in Immunology, 2022)
Bladder cancer (BCa) is the tenth most commonly diagnosed cancer worldwide and cellular senescence is defined as a state of permanent cell cycle arrest and considered to play important roles in the development and progression of tumor. But the comprehensive effect of senescence in BCa has not ever been systematically evaluated. Using the CRISPR-Cas9 screening data acquired from Depmap (Cancer Dependency Map), senescence genes from the CellAge database and gene expression data from The Cancer Genome Atlas (TCGA), we screened out 12 senescence genes which might play critical roles in BCa. A four-cell-senescence-regulator-gene prognostic index was constructed using the least absolute shrinkage and selection operator (LASSO) and multivariate COX regression model. The transcriptomic data and clinical information of BCa patients were downloaded from TCGA and Gene Expression Omnibus (GEO). We randomly divided the patients in TCGA cohort into training and testing cohort and calculating risk score according to the expression of the four senescence genes. The validity of this risk score was validated in testing cohort (TCGA) and validation cohort (GSE13507). The Kaplan-Meier curves revealed a significant difference in the survival outcome between the high and low risk score groups. A nomogram including the risk score and other clinical factors (age, gender, stage and grade) was established with better predictive capacity of OS in 1, 3, and 5 years. Besides, we found patients in the high risk group had higher tumor mutation burden (TMB), lower immune, stroma, and ESTIMATE scores, higher tumor purity, aberrant immune functions, and lower expression of immune checkpoints. We also performed GSVA and GSEA analyses to investigate the interaction between risk score and hallmark pathways and found high risk score was connected with activation of senescence related pathways. Furthermore, we found high risk score was related to better response to immunotherapy and chemotherapy. In conclusion, we identified a four-cell-senescence-regulator-gene prognostic index in BCa and investigated its relationship with TMB, the immune landscape of TME and response to immunotherapy and chemotherapy, and we also established a nomogram to predict the prognosis of patients with BCa.